Kondisi Kegiatan Keagamaan Muslim Perempuan pada Masa Pandemi Covid-19 di Wilayah Suburban - Rina Febriyani; M Taufiq Rahman; M Yusuf Wibisono (UIN Sunan Gunung Djati Bandung, 2021)
This study aims to explain the differences in the religious attitudes of Muslim women before and during the Covid-19 pandemic and to explain the various challenges faced by Muslim women in dealing with the Covid-19 pandemic in Cinanjung Tanjungsari Village, Sumedang, West Java. The method used in this paper is descriptive-analytical with a qualitative approach. The process of data collection is done through observation, interviews, and documentation. This study uses the Adaptation, Goal Attainment, Integration, and Latency (AGIL) theory from Talcott Parsons. The findings of this study are, first, the adaptation process carried out by Muslim women when carrying out religious routines during the Covid-19 pandemic is by implementing health protocols following the recommendations of the local government. Second, the challenges that some Muslim women face during the Covid-19 pandemic are the limited ability to operate technology as a medium for worship activities, work, and study. However, the 'force' to master technology has caused Muslim women to slowly get to know social media and start to be able to operate it. Third, the impact of the Covid-19 pandemic has caused changes to the religious diversity of Muslim women who are increasingly diligent and obedient in carrying out worship because of the unfavorable situation and conditions due to the pandemic. This study can provide insight into the extent of adaptation of society, especially women, to the Covid-19 outbreak in a suburban area.